Effect of Thermal Mismatch on Fracture Characteristics of Porcelain Veneered Lithia-Based Disilicate Posterior Ceramic Crown - Ja-Young Kim; Yu-Kyoung Kim; Won-Suk Oh; Tae-Sung Bae; Jung-Jin Lee; Min-Ho Lee; Yong-Seok Jang; Seung-Geun Ahn (Applied Sciences)
(1) Background: Dental glass–ceramics shrink during crystallization, complicating restoration manufacturing. Thermo-pressure molding was introduced to address this, with lithium disilicate crystals providing high strength. Residual tensile stresses can influence the chipping strength of single tooth crowns. (2) Methods: Insync dentine was layered onto three lithia-based disilicate core ceramics (Amber Press, IPS e.max Press) for microtensile bond strength tests. The Vickers test assessed the residual tensile stress and interfacial bonding. Porcelain-veneered posterior ceramic crowns were fabricated and subjected to axial loading, measuring fracture loads (three per group). (3) Results: A chemical bonding layer formed at the interface, which was thicker in the Insync-IPS e.max Press and increased with more firings. The ultimate tensile bond strength was 28.5 MPa for the four-times-fired Insync-Amber Press, similar to the twice-fired Insync-IPS e.max Press. No residual tensile stress was found in the Insync-Amber Press; the Insync-IPS e.max Press showed crack growth within 250 μm of the bonded interface. The average fracture resistance was twice as high for the Insync-Amber Press. (4) Conclusions: The Insync-Amber Press exhibited better thermal harmony with no crack growth, while the IPS e.max Press showed crack growth due to residual tensile stress. Insync-Amber Press posterior ceramic crowns had significantly greater fracture resistance than Insync-IPS e.max Press crowns.